Multiple‐Resonance Extension and Spin‐Vibronic‐Coupling‐Based Narrowband Blue Organic Fluorescence Emitters with Over 30% Quantum Efficiency. Issue 33 (17th July 2022) - Lee, Ha Lim; Jeon, Soon Ok; Kim, Inkoo; Kim, Seung Chan; Lim, Junseop; Kim, Joonghyuk; Park, Sangho; Chwae, Jun; Son, Won‐Joon; Choi, Hyeonho; Lee, Jun Yeob
Abstract: Achieving narrow‐bandwidth emission and high external quantum efficiency (EQE) simultaneously is a challenge for next‐generation blue‐emitting organic light‐emitting diodes (OLEDs). In this study, novel multiple‐resonance thermally activated delayed fluorescence (MR‐TADF) emitters are developed by fusing an indolocarbazole unit with two carbazole skeletons using para ‐oriented nitrogen atoms. The resulting rigid and planar π‐system without electron‐accepting atoms exhibits pure blue photoluminescence at 470 nm, reaching a 100% quantum yield with a full‐width‐at‐half‐maximum (FWHM) of 25 nm. Higher‐level quantum chemistry calculations confirm an MR effect within the extended π‐conjugation and an enhanced triplet‐to‐singlet crossover (10 4 s −1 ) through a reduced energy gap (Δ E ST ) coupled with large spin‐vibronic coupling mediated by low‐lying triplet excited states. An OLED fabricated using the MR‐TADF emitter with CIE color coordinates of (0.12, 0.16) exhibits a record high EQE of 30.9% and a small FWHM of 23 nm. With further optimization of the device structure, a high EQE of 33.8% is achieved without additional outcoupling enhancements owing to the near‐perfect horizontal alignment of the emitting dipoles. Abstract : An indolo[3, 2, 1‐ jk ]carbazole‐derived extended multiple‐resonance structure, driven by the spin‐vibronic model, is designed to reduce the gap between the singlet and triplet excited states and to increase absolute photoluminescence quantum yield. Pure blue organic‐light‐emitting diodes with a high external quantum efficiency over 30% and a narrow full‐width‐at‐half‐maximum of 23 nm are realized with extended multiple‐resonance emitters.